Impact of atmospheric deposition on N and P geochemistry in the southeastern Levantine basin - Carbo, P; Krom, MD; Homoky, W; Benning, L; Herut, B (2005)
Aeolian dust was collected from 2001 to 2003, as part of a longer-term study, to estimate the nutrient input to the Levantine basin from atmospheric deposition. Adsorption experiments, using dust samples from six individual dust storms, showed insignificant adsorption of phosphate onto dry deposited Saharan dust. Thus adsorption onto dust can be discounted as a reason for the high nitrogen:phosphorus (N:P) ratio in the deep water of the eastern basin. A single dust storm sample from the Western Mediterranean was able to adsorb some phosphate from seawater, and it is speculated that this may be linked to the action of acid aerosols on the dust during cloud formation, or to the varying chemical composition in different sources of dust. Dry atmospheric deposition is an important net supplier of both N and P to the eastern basin. Leachable inorganic nitrogen concentrations and fluxes are higher in background (non-storm) samples than in storm samples, probably due to the smaller grain size and aerosol source. Total P is supplied naturally with the dust, as shown by the close correlation between total P and Al (r2=0.95). However, there is a poor correlation between leachable inorganic P (LIP) and Al (r2=0.20), which may be related to grain-size effects and/or recycling processes in the atmosphere. Even so, the supply of LIP to surface waters is greatest during dust storms due to comparatively high deposition of aerosol material. While atmospheric input of P during dust storms does not produce significant in situ increases in chlorophyll, probably due to rapid microbial grazing, it does represent an important proportion of the long-term nutrient input to the basin. This may be increasing as the frequency of dust storms increases. © 2005 Elsevier Ltd. All rights reserved.